Excerpt from "The Gospel According to Jesus Queen of Heaven" - Clifford, Jo (Journal of feminist studies in religion, 2018)
This extract is from the play "The Gospel According to Jesus Queen of Heaven." In winter 2017, the play was performed in Brazil and Uruguay; it will be revived in Scotland in 2018.